PENINGKATAN KREATIVITAS PESERTA DIDIK MENGGUNAKAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING DENGAN MODEL PEMBELAJARAN PROJECT BASED LEARNING - Ipinda Intan Saliya; Yantoro Yantoro; Misnawati S; Basyir Basyir (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2024)
This study aims to evaluate the effectiveness of Culturally Responsive Teaching and Project Based Learning approaches in improving the learning creativity of grade 4 students at SDN 42/IV Jambi City during Mathematics learning. The research was conducted using the classroom action research method, with data collected through direct observation of student learning activities during three cycles of action, as well as filling out a learning motivation questionnaire by 28 students. At the beginning of the study, only 14.2% of students had high learning creativity, 35.7% were in the medium category, and 50% had low learning motivation. Through the application of CRT approach and PjBL model, students' participation and involvement in learning increased significantly. In the final cycle, the average student learning motivation score increased from 58 to 82, indicating a consistent increase in student learning creativity. These findings show that the CRT approach and PjBL model are effective in slowly increasing students' creative learning. They also highlight how important it is to consider students' cultural context when making good and relevant learning strategies. Teachers can create an inclusive learning environment by using their cultural background as a learning resource.